(untitled) (The Review of Diabetic Studies, 2025)
Background: Diabetes mellitus represents one of the most prevalent chronic diseases worldwide, posing significant public health challenges, especially in the Kingdom of Saudi Arabia, where the prevalence rate ranks among the highest globally. The escalating burden of diabetes underscores the urgent need for innovative, nurse-led approaches that integrate clinical knowledge, psychological support, and digital technologies to enhance patient outcomes and align with the national Vision 2030 Health Transformation Strategy. Purpose: This narrative review explores nursing strategies and innovations in diabetes management, focusing on three interrelated domains: nurses’ knowledge and competency, nurse-led psychological interventions, and digital health applications. Methods: A comprehensive literature search was conducted using PubMed, Scopus, CINAHL, and Google Scholar for studies published between 2019 and 2024. Keywords included “nursing,” “diabetes management,” “psychological interventions,” and “digital health.” Studies were selected if they examined nursing roles, educational interventions, or digital tools that contribute to improving diabetes care outcomes. Results: Findings reveal that Saudi nurses demonstrate strong clinical commitment but variable knowledge and confidence in diabetes care. Continuous professional education, simulation-based training, and structured diabetes modules were associated with improved performance. Nurse-led psychological interventions—such as motivational interviewing and behavioral counseling—were found to reduce diabetes distress and improve adherence. Moreover, the integration of digital platforms (e.g., Sehhaty, Wasfaty, Mawid) significantly enhanced communication, remote monitoring, and self-management. Conclusion: Integrating knowledge, psychological, and digital interventions within nursing practice offers a holistic framework for improving diabetes outcomes in Saudi Arabia. Empowering nurses through education, psychological training, and digital competency aligns with Saudi Vision 2030 priorities for sustainable, patient-centered, and technology-driven healthcare. Future policies should focus on expanding nurse-led clinics, enhancing interdisciplinary collaboration, and fostering innovation to ensure that diabetes management becomes both comprehensive and compassionate.